2017
DOI: 10.1007/s10943-017-0437-6
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Spirituality and Spiritual Care among Muslim Nurses in Indonesia

Abstract: This cross-sectional study was conducted to examine 256 Muslim nurses' perception of spirituality and spiritual care in Indonesia. The Spirituality and Spiritual Care Rating Scale (SSCRS) was translated and culturally adapted. Moderately high degrees in five domains and total SSCRS were found. Specialty, education level, clinical seniority, having spiritual training, and previous spiritual caring experience could impact on the SSCRS. Most nurses have cared for patients with spiritual needs, but denied having a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 33 publications
2
41
1
2
Order By: Relevance
“…While there is extensive Western literature on spirituality/religion in palliative care, the literature from Indonesia is limited. Only four studies could be identified related to spirituality/religion in the general care setting, three studies explored perceptions and attitudes of health‐care professionals toward spirituality (Herlianita, Yen, Chen, Fetzer, & Lin, ; Lucchetti et al ., ; Ramakrishnan et al ., ), and one study measured spirituality in patients with coronary heart disease (Ginting, Naring, Kwakkenbos, & Becker, ). These studies do not provide a picture of spirituality/religious factors in play in the palliative care context.…”
Section: Introductionmentioning
confidence: 99%
“…While there is extensive Western literature on spirituality/religion in palliative care, the literature from Indonesia is limited. Only four studies could be identified related to spirituality/religion in the general care setting, three studies explored perceptions and attitudes of health‐care professionals toward spirituality (Herlianita, Yen, Chen, Fetzer, & Lin, ; Lucchetti et al ., ; Ramakrishnan et al ., ), and one study measured spirituality in patients with coronary heart disease (Ginting, Naring, Kwakkenbos, & Becker, ). These studies do not provide a picture of spirituality/religious factors in play in the palliative care context.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receive palliative care in different cultures and societies; so, despite the commonality of human nature, they will differ in terms of their spirituality, culture and beliefs [32][33][34]. Therefore, different strategies will need to be applied to provide a more effective care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the definition of spirituality in Herlianita et al (2018) is as follows: "Spirituality has been identified with three common elements: transcendence, connectedness of self/ others/ nature/ higher power, and meaning in life (Weathers et al 2016). It promotes a personal search for meaning and purpose in life (Beauregard and O'Leary 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although spirituality is rooted in a religious experience and emphasizes a relationship with a transcendent superior being, it may or may not be related to religion or religious practices (Tanyi 2002). (Herlianita et al, 2018) Considering this, the author puts Paul Tillich's (1951) study explaining that spirituality and religion is very relevant to motivation, because motivation generally reflects on human's main apprehension, deepest motive and finally giving great potency to human health (Oman, 2018). Therefore, in addition to identifying the cause of disease socioculturally, Religious and Spirituality function as motivator for human's healing with positive effect exerted.…”
Section: Discussionmentioning
confidence: 99%